2005
DOI: 10.1159/000082399
|View full text |Cite
|
Sign up to set email alerts
|

Plant chromosome homology: hypotheses relating rendezvous, recognition and reciprocal exchange

Abstract: Many higher eukaryotes have dispersed repetitive DNA and multiple instances of segmental duplications. As well, many plants and lower animals are polyploids. Thus restricting reciprocal genetic exchange to truly homologous chromosomes is likely a multi-step process. We propose the following sequence of events. First the ability to form a synaptonemal complex (SC) prematurely (i.e. before homology checking/recognition) is precluded by the organization of chromosomes during premeiotic S phase. Next rough alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 146 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…However, in many organisms homologous pairing has been found to be independent of recombination [45], as must be partially the case also in potato, where genetic recombination is repressed in the heterochromatin [21,29]. Alternatively, it has been proposed that the rough alignment of the synaptonemal complex depends on bringing together key allelic transcription units [48]. …”
Section: Discussionmentioning
confidence: 99%
“…However, in many organisms homologous pairing has been found to be independent of recombination [45], as must be partially the case also in potato, where genetic recombination is repressed in the heterochromatin [21,29]. Alternatively, it has been proposed that the rough alignment of the synaptonemal complex depends on bringing together key allelic transcription units [48]. …”
Section: Discussionmentioning
confidence: 99%
“…The RNA-binding proteins Mei2 and Mmi1 form foci at the sme2 locus, and Mmi1 negatively regulates pairing (41), implicating both DNA-RNA and RNA-protein interactions in this process. To date, there is no clear evidence to support the notion that RNA transcripts may mediate homologous chromosome pairing in other organisms, but meiotic-specific RNA transcripts distributed over each homolog could assist in the homology search and pairing processes (62,137,139). An intriguing hypothesis is that centromeric and possibly heterochromatic regions in general could represent such sites.…”
Section: Roles For Heterochromatin and Rna In Meiotic Homologous Chromentioning
confidence: 99%
“…Involvement of allelic transcription units is also suggested for pairing in polyploids (Wilson et al 2005). (3) High-resolution cytology on GFP-tagged loci of living Drosophila cells showed that homologous interactions correspond to random, diffuse walk motion.…”
Section: Premeiotic Pairingmentioning
confidence: 99%